Afterword: Islamic bureaucracies, bureaucrats, and bureaucratisation - Bruinessen, Martin van (Religion, state & society, 2025)
In the afterword to this collection on Islamic bureaucracies the author focuses on some of the main themes that are explicitly or implicitly addressed in most of the contributions. These include the nexus of secularisation and bureaucratisation, the ‘deprivatisation’ of religion as Islam has resumed a prominent presence in the public sphere, the interaction of state and non-state bureaucracies administering Islam, the surveillance of religious practices and the ‘bureaucratic incorporation’ of those surveilled, and the expansion of national religious bureaucracies to engage with diaspora populations. This is followed by a few comments on the heterodox groups that are excluded from the administrative reach of the religious bureaucracies, such as the Alevis in Turkey and Kebatinan groups in Indonesia.